Systematic Review of Augmented Reality Applications in Wayang Heritage Preservation - Hermawan, Hellik; Saputra, Dhanar Intan Surya; Albana, Ilham; Ramadhan, Muhammad Bintang; Mustofa, Dinar (Universitas Bina Darma, 2025)
This study presents a systematic literature review on Augmented Reality (AR) in Wayang from 2020 to 2025. AR has become an innovative solution that combines education and entertainment to increase the engagement of the younger generation and expand access to traditional Wayang art. This study examines the trend of AR in Wayang, including design approaches and user interaction strategies, as well as the benefits and challenges of implementing this technology. It also identifies research gaps and future development directions. This review discusses explicitly the application of AR to various forms of Wayang, including Wayang Kulit, Wayang Golek, and other traditional variants, while excluding Virtual Reality (VR) and other digital art forms. The results indicate that AR applications based on mobile platforms with gesture interaction and gamification effectively enrich the user experience in digital Wayang performances. However, significant challenges related to technological limitations, cultural sensitivity, and involvement of indigenous communities still need to be overcome. This study recommends a multidisciplinary and collaborative approach to developing AR Wayang, enabling authentic and sustainable cultural preservation. These findings are expected to serve as the basis for inclusive digital cultural innovation, which will have a positive impact on preserving Wayang's cultural heritage.